2006
DOI: 10.1128/ec.5.2.301-312.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ebs1p, a Negative Regulator of Gene Expression Controlled by the Upf Proteins in the Yeast Saccharomyces cerevisiae

Abstract: Mutations in EBS1 were identified in Saccharomyces cerevisiae that cosuppress missense, frameshift, and nonsense mutations. Evidence from studies of loss of function and overexpression of EBS1 suggests that Ebs1p affects gene expression by inhibiting translation and that a loss of EBS1 function causes suppression by increasing the rate of translation. Changes in EBS1 expression levels alter the expression of wild-type genes, but, in general, no changes in mRNA abundance were associated with a loss of function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 55 publications
2
28
1
Order By: Relevance
“…As described earlier, ScEbs1 but not ScEst1 has been shown to render yeast cells rapamycin sensitive, possibly through a role in the NMD pathway (14,24). We therefore analyzed the rapamycin sensitivity of our KlEst1 mutants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described earlier, ScEbs1 but not ScEst1 has been shown to render yeast cells rapamycin sensitive, possibly through a role in the NMD pathway (14,24). We therefore analyzed the rapamycin sensitivity of our KlEst1 mutants.…”
Section: Resultsmentioning
confidence: 99%
“…In S. cerevisiae, an EST1 homologue named EBS1 (Est1-like Bcy1 Suppressor) was shown to play a modest role in telomere maintenance but also to regulate translation and non-sense-mediated decay (NMD) (14,24,54). Specifically, the ebs1⌬ mutant manifests higher levels of NMD-targeted RNAs and greater resistance to rapamycin, which inhibits the TOR signaling pathway that regulates cell growth and translation.…”
mentioning
confidence: 99%
“…we asked whether Ebs1p, a translation repressor that is down-regulated by the NMD pathway (Ford et al 2006), affects translation of the spliced GpII-CUP1 transcripts. Again, neither the ebs1 nor the ebs1 upf1 mutations suppressed the translation defect of the spliced GpII-CUP1 RNA (Fig.…”
Section: Spliced Group II Intron Transcripts Are Poorly Translatedmentioning
confidence: 99%
“…We also showed that the lsm6, nup159 and ebs1 alleles did not alter the abundance of CCR4-NOT complex components, indicating that their effects were not indirectly through lowering CCR4 and CAF1 abundance in the cell. In addition, the role of EBS1 in negatively regulating translation [30] cannot directly explain how it would function as an activator of ADH2. spt10 results in a low level of ADH2 expression under glucose growth conditions by an unknown mechanism that could involve affecting ADH2 chromatin structure [2,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Its involvement in nonsense mediated decay may be only one means that its is involved in mRNA expression, as it has also been demonstrated that EBS1 binds eIF4E, the mRNA cap binding protein required for translational initiation. In fact, EBS1 is a negative regulator of translation [30]. EBS1 also binds DCP1 [31], a component of the mRNA decapping complex [20].…”
Section: Cloning Of Asg2 3 Andmentioning
confidence: 99%